Characteristics of Educational Leaflets that Attract Pregnant Women - Noriko Sudo (SAGE Publishing, 2011)
Background Many health service sectors produce leaflets for health education, but specific issues such as their overall content and design (layout, graphics, illustrations) are seldom discussed. Important features contributing to the effectiveness of any leaflet is the extent to which it is read by its target audience. The purpose of this study was to examine the acceptability of two different leaflets on abstinence from alcohol during pregnancy. Methods Four semistructured group discussions were conducted among 33 pregnant women. They were asked if they would take, read, and save the leaflets, and to give a reason for their decision. The reasons were discussed according to the components of the leaflet, including its front cover, content, and illustrations. Results The design of a leaflet's front cover plays a key role in attracting pregnant women, and, in the event that readers are interested in the topic, they prefer a leaflet with detailed content, and a real-life example, eg, a photograph of a child with fetal alcohol syndrome. Conclusion Positive key characteristics should be incorporated into educational leaflets to enhance the attention given to the material by pregnant women, as well as to facilitate retention of the information.